ANALYSIS OF STUDENTS’ BEHAVIOUR DURING INTERNET USE WHILE REGARDING THEM AS POTENTIAL FUTURE E-COMMERCE USERS - Marošan, Zoran T (International Journal of Economic Practice and Policy, 2016)
The development of the ICT (Information and Communications Technologies) in the last two decades and their implementation in business has brought important changes in almost every field of human activity. Commerce is certainly one of those that experienced the most significant modifications leading to the appearance of E-commerce. The successful application of E-commerce depends on many factors, most of them are related to the level of ICT infrastructure development and the use of the ICT in the country. This paper shows some of the most important indicators related to the ICT and their use as well to the Internet and its use. First set of data is gathered using a questionnaire filled by the students of  Novi Sad Business School. Comparing it with the matching data for Serbia and  28 countries of European Union, the author of this paper drew some conclusions regarding  Novi Sad Business School students as possible future E-commerce users.
Keywords: ICT; INTERNET; E-commerce